"Gay Guys are Shit-Lovers" and "Lesbians are Obsessed With Fingers": The (Mis)Representation of LGBTIQ People in Thai News Media. Issue 2 (28th January 2019) - Fongkaew, Kangwan; Khruataeng, Anoporn; Unsathit, Sumon; Khamphiirathasana, Matawii; Jongwisan, Nisarat; Arlunaek, Oranong; Byrne, Jensen
ABSTRACT: This article presents an analysis of news reports containing information or opinions about lesbian, gay, bisexual, transgender, intersex, and queer (LGBTIQ) people taken from six Thai media outlets over a period of one year. The aim was to explore how LGBTIQ people are portrayed in news media narratives. LGBTIQ identities were found to be vastly underrepresented and, when represented, were often represented inaccurately, stereotypically, harmfully, or without a clear understanding of the diversity of sexual orientations, gender identities, and gender expressions. (Hetero-)sexist narratives, negative portrayals, harmful stereotypes, and discriminatory speech were also widely found, fueling a climate of stigmatization and discrimination of LGBTIQ people in Thai society. This article suggests that key stakeholders in Thai news media should be sensitized on the human rights of LGBTIQ people and on basic professional ethics in journalism.